Web-Based Brokerage System Development - Al-Farsi, Mohammed Ahmed (2003)
Electronic Commerce (ecommerce) depends on the emergence of capabilities that empower buyers to obtain the product data they need to make informed purchase decisions, quickly and easily. Traditional physical markets are often brokered by intermediaries that facilitate market transitions by providing brokerage services. In the global Internet Electronic Brokers provide a central marketplace, and provide many essential third party services. Electronic Brokerages are regarded as the core functionality in overcoming many current limitation of Internet Commerce. Also, search costs, lack of privacy, incomplete information, contracting risk, and pricing are better managed with Electronic Brokers. However, Brokers are currently facing the problem of combining all the information within a single coherent structure through which buyers can navigate readily. This is due to the lack of interoperability standards between ecommerce applications, which leads to high costs for the brokers. The research is to design a framework for building a web-based brokerage system. The system plays a central role in allowing service providers to publish and advertise their offer and at the same time helping the consumer to access easily and in a moderate manner the offered services and information and try to solve the problem of interoperability. Consumer Buying Behavior model which consists of six stages that defines the decision process and acts of people involved in buying and using products had been applied in the design of the system. In addition to offering many essential third party services, the system offers some tasks, which simplify the functionality of brokers, which override the limitations of Internet e-commerce. Client-server communication that uses 3-tier architecture had been used to override the 2-tier limitations and enhance the security features of the system. To achieve the requirements of such as online e-commerce application Java servlets with JDBC on the server side, HTML and JavaScript on the client side are used. Unified Modeling Language (UML) had been applied in order to determine system structure and system behavior from user/system requirements. The study shows that online brokerage can replace traditional brokers with additional functionality. By designing reusable components and using certain tools will try to solve Interoperability problem between ecommerce applications. Java servlets shown as a powerful tool to be used on server side in this type of application which can help to override some limitations of Internet e-commerce.